2018
DOI: 10.1126/sciimmunol.aan8884
|View full text |Cite
|
Sign up to set email alerts
|

The receptor repertoire and functional profile of follicular T cells in HIV-infected lymph nodes

Abstract: Follicular helper CD4+ T cells (TFH) play an integral role in promoting B cell differentiation and affinity maturation. While TFH cell frequencies are increased in lymph nodes (LN) from individuals infected with HIV, humoral immunity remains impaired during chronic HIV infection. Whether HIV inhibits TFH responses in LNs remains unclear. Advances in this area have been limited by the difficulty of accessing human lymphoid tissues. Here, we combined highdimensional mass cytometry with TCR repertoire sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…4B). (Lindqvist et al, 2012;Matthieu et al, 2013;Wendel et al, 2018), we tested if CXCR5 -PD-1 + T cells are also enriched for T cells that recognize HIV-derived antigens. To do this, we stimulated total LN cells with Gag peptides for 18 hours and identified peptide-specific T cells within naïve, CXCR5 -PD-1 -, CXCR5 -PD-1 + , or CXCR5 + PD-1 + T cells by CD25 and OX40 upregulation (Dan et al, 2016).…”
Section: Cxcr5 -Pd-1 + T Cells Shared Hiv-specificity and Tcr Sequencmentioning
confidence: 99%
“…4B). (Lindqvist et al, 2012;Matthieu et al, 2013;Wendel et al, 2018), we tested if CXCR5 -PD-1 + T cells are also enriched for T cells that recognize HIV-derived antigens. To do this, we stimulated total LN cells with Gag peptides for 18 hours and identified peptide-specific T cells within naïve, CXCR5 -PD-1 -, CXCR5 -PD-1 + , or CXCR5 + PD-1 + T cells by CD25 and OX40 upregulation (Dan et al, 2016).…”
Section: Cxcr5 -Pd-1 + T Cells Shared Hiv-specificity and Tcr Sequencmentioning
confidence: 99%
“…Analysis of BCR repertoire post-immunization (Scheid et al, 2009;Sundling et al, 2014) Study T cell clonal expansion in vivo in the context of HIV infection (Wendel et al, 2018) Integration sequencing Mapping of integrated vDNA Map HIV-1 integration sites in the CD4 + T cell genome of primary samples (Cohn et al, 2015) Virus barcoding Engineered viruses with degenerate unique barcodes Examine the transcriptional potential of integrations sites by correlating barcodes in integrated DNA and vRNA High dimensional phenotyping…”
Section: Profiling Of the B Cell And T Cell Repertoiresmentioning
confidence: 99%
“…Other studies attributed B cell dysfunction to inefficient help provided from germinal center follicular T cells (GC T FH ) (Cubas et al, , 2015Boswell et al, 2014). The analysis of lymph node samples from untreated HIV-1 + donors by combined high dimensional mass cytometry and TCR repertoire singlecell sequencing shed light on the fine structure of these T FH responses (Wendel et al, 2018), revealing that HIV-1-specific T FH expand but become functionally skewed with limited TCR diversity, features that correlate with B cell dysregulation in the same lymph node.…”
Section: Immune Response and Immune Dysfunctionmentioning
confidence: 99%
“…Most of these cellular processes are only briefly, or not at all, detectable in peripheral blood. Gathering information from human lymph nodes after antigen exposure can be problematic depending on node accessibility, size, and the extent of the response, although there have been some studies in which biopsies have been used to study lymph node-based responses [ 115 , 116 ]. NHP studies have shown that analysis of lymph node fine needle aspirates can better predict neutralizing HIV env vaccine response [ 117 , 118 ].…”
Section: Modeling Immune Tissuesmentioning
confidence: 99%